Choanal atresia in a Newfoundland puppy - Evans, Katie (Katharine G.) (2004)
This report discusses the diagnosis and treatment of membrano-osseous choanal atresia in a Newfoundland puppy. Diagnosis was made via computed tomography and flexible rhinoscopy. An attempt was made at surgical correction by choanoplasty via a transpalatal approach. Endoscopic examination four weeks post-operatively showed that the surgical site had stenosed, with the left side more affected than the right. A balloon choanplasty was performed on the right side, but was unsuccessful on the left due to inability to break down the fibrous stenotic membrane. Clinical signs recurred, and four weeks subsequent to the first balloon choanoplasty, the procedure was repeated on the right side, achieving 90% patency. The fibrous membrane on the left side was broken down with Steinmann pins passed nasally through a rigid rhinoscope, achieving 60% patency. This paper discusses the clinical presentation of this patient, differential diagnoses for the presenting complaints, diagnostic workup of the case, and comparative medicine of the disorder.